A coating material against calcium sulfate scale and its preparation method and application
Patent Information
- Application Number
- CN202611164466.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-30
AI Technical Summary
现有锌基防垢技术存在以下明显缺陷:锌基合金材料成本高昂、施工局限性大;锌离子释放不可控,初期释放速率过快易造成水体锌离子超标污染,后期释放衰减过快导致防垢寿命短;缺乏精准的离子释放调控机制与量化模型,无法适配长期稳定的工业防垢工况,工程适用性受限
1.锌离子释放可控可量化:本发明实施例通过引入具有规整微孔结构的分子筛作为控释调节组分,利用其微孔限域效应精准调控锌离子缓释速率,可将锌离子稳态释放速率稳定控制在一定范围内,有效克服了传统锌基材料初期暴释、后期衰减过快的问题,实现长效匀速释放。
Smart Images

Figure SMS_1 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of industrial anti-scaling and surface engineering technology, specifically relating to an anti-calcium sulfate scale coating material, its preparation method, and its application. Background Technology
[0002] When industrial equipment operates in water systems containing high concentrations of calcium and sulfate ions, calcium sulfate scale easily forms on the inner walls of the equipment. Calcium sulfate scale is hard, has strong adhesion, and extremely low thermal conductivity, significantly reducing the heat transfer efficiency of heat exchange equipment, increasing system energy consumption, and in severe cases, causing equipment blockage, leading to system shutdowns and increased maintenance costs. Power plant desulfurization wastewater and high-hardness circulating cooling water systems, with their high concentrations of calcium and sulfate ions and pronounced calcium sulfate scaling tendency, represent a key challenge in industrial water treatment.
[0003] Existing zinc-based anti-scaling technologies mainly utilize zinc-based alloy plates and zinc-based passivation layers, relying on the slow release of zinc ions to achieve scale inhibition. Studies have shown that Zn²⁺… + It can effectively reduce the nucleation rate and crystal directional growth rate of calcium sulfate, and has good calcium sulfate scale inhibition performance. Summary of the Invention
[0004] This invention is based on the inventor's discoveries and understanding of the following facts and problems: Existing zinc-based anti-scaling technologies suffer from the following significant drawbacks: high cost of zinc-based alloy materials and limited application possibilities; uncontrollable zinc ion release, with excessively rapid initial release rates leading to excessive zinc ion pollution in water bodies, and rapid decay in later release resulting in short anti-scaling lifespan; and a lack of precise ion release control mechanisms and quantitative models, making them unsuitable for long-term stable industrial anti-scaling conditions and limiting their engineering applicability. Therefore, developing an anti-calcium sulfate scale coating material with controllable zinc ion release, adaptability to high-salt, high-hardness wastewater conditions, and a matching dynamic release model has significant engineering application value and theoretical research significance.
[0005] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, embodiments of this invention provide an anti-calcium sulfate scale coating material, its preparation method, and its application.
[0006] In a first aspect, embodiments of the present invention provide an anti-calcium sulfate scale coating material, the anti-calcium sulfate scale coating material comprising the following components: (1) Film-forming matrix material: The film-forming matrix material is bisphenol A type epoxy resin; (2) Zinc ion active component: The zinc ion active component is selected from at least one of zinc powder, zinc oxide, zinc sulfate and zinc nitrate; the amount of zinc ion active component added is 5wt% to 30wt% of the mass of the film-forming matrix material based on the mass of zinc element (that is, the mass of zinc element in the zinc ion active component accounts for 5wt% to 30wt% of the mass of the film-forming matrix material). (3) Controlled-release regulating component: The controlled-release regulating component is a molecular sieve; the amount of the controlled-release regulating component added is 2wt% to 15wt% of the mass of the film-forming matrix material; (4) Curing and crosslinking components: The curing and crosslinking components are selected from amine curing agents and / or acid anhydride curing agents; the amount of the curing and crosslinking components added is 15wt% to 25wt% of the mass of the film-forming matrix material; (5) Inert diluent: The inert diluent is a mixture of xylene and n-butanol; The amount of the inert diluent added is 5 wt% to 20 wt% of the mass of the film-forming matrix material.
[0007] The advantages and technical effects of the anti-calcium sulfate scale coating material of this invention are as follows: 1. Controllable and quantifiable zinc ion release: In this embodiment of the invention, a molecular sieve with a regular microporous structure is introduced as a controlled-release regulating component. By utilizing its microporous confinement effect, the zinc ion slow-release rate can be precisely controlled within a certain range. This effectively overcomes the problems of rapid initial release and excessively fast decay in the later stage of traditional zinc-based materials, and achieves long-term uniform release.
[0008] 2. High scale inhibition efficiency and long-lasting effect: The embodiments of this invention utilize the micropore confinement and slow-release mechanism of molecular sieves to achieve Zn²⁺ scale inhibition. + Uniform and long-lasting release, inhibiting calcium sulfate scale formation through a dual synergistic mechanism of crystal nucleation inhibition and crystal distortion, significantly improving the calcium sulfate scale inhibition rate, which is significantly superior to ordinary zinc-based coatings without controlled-release regulating components. The coating in this embodiment exhibits no peeling or powdering. (Zn²) + It exhibits excellent release stability.
[0009] 3. Predictable and environmentally friendly ion release: The zinc ion release behavior of the anti-calcium sulfate scale coating conforms to Fick's diffusion law. The cumulative release amount at different times can be accurately predicted through a dynamic release model (M0, k parameters). The effective lifespan of the anti-scaling coating can be predicted based on actual water quality conditions, and the amount of zinc ions released into the water can be predicted, effectively avoiding the risk of excessive zinc ion discharge and ensuring water safety.
[0010] 4. Simplified composition and controllable cost: The raw materials of the embodiments of the present invention are widely available and the cost is controllable. The preparation process is simple and the construction is convenient. It is suitable for large-area anti-scaling coating on the inner walls of industrial equipment that are prone to scaling, such as power plant desulfurization wastewater treatment systems, circulating cooling water systems, heat exchange equipment and pipelines.
[0011] 5. Wide applicability and customizable control: By adjusting the type and amount of controlled-release regulating components (2wt%~15wt%), the type of zinc ion active components (zinc oxide for low-speed slow release, zinc sulfate / zinc nitrate for medium-speed slow release), and the zinc loading (5wt%~30wt%), this invention can flexibly adapt to the differentiated needs of various scaling conditions, making it highly applicable to engineering projects.
[0012] Optionally, the film-forming matrix material is selected from bisphenol A type E44 epoxy resin and / or bisphenol A type E51 epoxy resin. Choosing bisphenol A type E44 epoxy resin and / or bisphenol A type E51 epoxy resin as the film-forming matrix material mainly brings multiple advantages such as flexible processing, uniform dispersion, adjustable controlled release, and reliable protection: the viscosity difference between the two allows for flexible adaptation to different construction methods such as spraying and brushing, and they have good wetting and dispersibility for zinc ion controlled release composite powder, ensuring uniform distribution of the zinc component in the coating; simultaneously, the different epoxy values of the two allow for the formation of matrices with different densities after crosslinking with the curing crosslinking components, providing a material basis for finely adjusting the zinc ion release rate; furthermore, bisphenol A type epoxy resin itself has strong adhesion and good water resistance, ensuring long-term stable service of the coating in high-salt, high-hardness wastewater.
[0013] Optionally, the particle size of the zinc ion active component is 300–800 mesh. Setting the particle size of the zinc ion active component to 300–800 mesh is primarily aimed at balancing dispersion uniformity, loading efficiency, and release controllability: this mesh size corresponds to a moderate particle size, allowing for uniform dispersion in the film-forming matrix without sedimentation or agglomeration, ensuring a dense and uniform coating structure; it also matches well with the micropores (average pore size approximately 1.8–3.2 nm) of the controlled-release regulating component after calcination, enabling the zinc ion active component to effectively embed into the pores of the controlled-release regulating component through a pre-loading process, avoiding initial explosive release due to excessive free zinc on the surface; simultaneously, this particle size facilitates the sand milling dispersion process, ensuring coating adhesion and long-term zinc release stability.
[0014] Optionally, the controlled-release regulating component is selected from NaY molecular sieves and / or 13X molecular sieves. The core advantage of selecting NaY molecular sieves and / or 13X molecular sieves as the controlled-release regulating component lies in their regular microporous structure and excellent adsorption performance, resulting in three major advantages: First, after calcination, the specific surface area is ≥600m² / g, providing sufficient loading sites for zinc ions and ensuring a long-term, sustained-release zinc source reserve; second, after calcination, it maintains regular microporous channels (average pore size approximately 1.8–3.2nm), allowing for precise control of the zinc ion diffusion rate through confinement effects, which is key to achieving steady-state zinc ion release; third, its pore size can be flexibly controlled by the calcination temperature (300–450℃). Low temperatures preserve intact channels to suit medium-to-high-speed zinc release, while high temperatures refine the channels to enhance confinement resistance to suit low-speed, long-term zinc release, enabling customized switching of release rates within the same material system. Furthermore, the aforementioned molecular sieves themselves exhibit good chemical stability and excellent compatibility with the epoxy resin matrix and zinc source, ensuring the structural integrity and zinc release stability of the coating during long-term service.
[0015] Optionally, the amine curing agent is selected from 650# polyamide curing agent and / or 651# polyamide curing agent; the anhydride curing agent is selected from methyltetrahydrophthalic anhydride and / or hexahydrophthalic anhydride. The key to selecting 650# polyamide curing agent and / or 651# polyamide curing agent, or methyltetrahydrophthalic anhydride / hexahydrophthalic anhydride, as the curing and crosslinking component lies in balancing the convenience of room-temperature curing with the adjustability of the coating crosslinking density, providing direct material support for controlling the matrix density of the zinc ion release rate. Specifically: Polyamide curing agents (650# amine value 200-240, 651# amine value 380-420) have moderate reactivity at room temperature, and the cured coating has good flexibility and strong adhesion to metals. They also have significant viscosity differences (3000-5000 vs 500-1000 mPa·s), allowing for flexible adjustment of the coating's application viscosity and working time. Anhydride curing agents (methyltetrahydrophthalic anhydride viscosity 50-80, hexahydrophthalic anhydride viscosity 110-130 mPa·s, both with purity ≥98%) have higher crosslinking density and better water and heat resistance after curing. They also produce no byproducts when reacting with epoxy resin, resulting in a denser coating. The difference between the two types of curing agents provides a direct means of "matrix density control" - a highly cross-linked and dense matrix can block water penetration and reduce the zinc ion dissolution rate. Appropriately reducing the degree of cross-linking can slightly increase the release rate, thereby achieving fine-tuning of the zinc ion release rate. Both support room temperature curing (12-24h), eliminating the need for heating equipment and significantly reducing on-site construction energy consumption and costs.
[0016] Optionally, in the inert diluent, the mass ratio of xylene to n-butanol is (5-9):(1-5). Choosing a mass ratio of xylene to n-butanol of (5-9):(1-5) as the inert diluent is crucial for balancing the solvent system's solubility, evaporation rate control, and application adaptability. Xylene is an excellent solvent for epoxy resins, exhibiting good dissolving and dispersing capabilities for both the film-forming substrate and the curing agent. n-Butanol, as a co-solvent and evaporation regulator, can slow down solvent evaporation, preventing excessively rapid surface drying of the coating and resulting in defects such as orange peel, pinholes, or powder agglomeration. Simultaneously, it helps the coating level and wet the metal substrate, improving adhesion. This ratio range provides a flexible adjustment window—a higher xylene ratio results in lower viscosity and faster drying, suitable for spray application; a higher n-butanol ratio leads to more gradual evaporation and better leveling, suitable for thick coating operations such as brushing or rolling. Furthermore, this compound system is non-reactive, does not interfere with the cross-linking reaction between epoxy resin and curing agent, and does not affect the slow-release behavior of zinc ions in the molecular sieve channels. While adjusting the viscosity of the coating during application, it can ensure the integrity of the coating structure and the long-term stability of zinc release performance.
[0017] Optionally, the steady-state zinc ion release rate of the anti-calcium sulfate scale coating material is 0.5–5.0 μg / (cm²·h). Setting the steady-state zinc ion release rate of the coating to 0.5–5.0 μg / (cm²·h) balances scale inhibition efficiency and environmental safety. When the steady-state zinc ion release rate is too low, the scale prevention effect is insufficient; when the steady-state zinc ion release rate is too high, it can easily lead to excessive zinc ion levels in the water. The aforementioned steady-state zinc ion release rate range can ensure that the calcium sulfate scale inhibition rate remains stable at over 89% while ensuring that the zinc ion concentration in the water remains within the safe threshold for a long period. Meanwhile, this range covers the actual needs of various scaling conditions, from circulating cooling water (0.5–2.0 μg / (cm²·h) in the low-speed section) to power plant desulfurization wastewater (2.0–5.0 μg / (cm²·h) in the high-speed section). It can achieve precise positioning through four-dimensional control of molecular sieve dosage, zinc source type, calcination temperature and coating thickness. Moreover, the fit degree between the release curve and the dynamic model is over 97.6%, making the release behavior quantifiable and predictable, which is convenient for precise industrial application and environmental compliance management.
[0018] Secondly, embodiments of the present invention provide a method for preparing an anti-calcium sulfate scale coating material, the preparation method comprising the following steps: S1. Pretreatment of controlled-release regulating component: The controlled-release regulating component is calcined at 300-450℃ for 2-4 hours and then naturally cooled to room temperature to obtain the calcined controlled-release regulating component; S2. Preloading of zinc ion active components: The zinc ion active components are dispersed in anhydrous ethanol to prepare a zinc-based dispersion with a mass fraction of 10% to 25%. The calcined controlled-release regulating components are added to the zinc-based dispersion, and the mixture is ultrasonically impregnated at room temperature for 30 to 60 minutes. Then, the mixture is stirred at room temperature at a speed of 300 to 400 r / min for 2 to 4 hours. After impregnation, the mixture is dried to obtain zinc ion controlled-release composite powder. S3. Mixing and dispersing the film-forming matrix material: Place the film-forming matrix material in a stirring vessel and stir at 200-300 r / min for 3-8 min at room temperature. Add the zinc ion controlled-release composite powder in batches, then stir at 500-600 r / min for 30-50 min, and then disperse by sand milling for 15-30 min to obtain the mixture. S4. Viscosity adjustment and modification: Add the inert diluent to the mixture to adjust the viscosity, stir evenly and then sieve to obtain the composite coating base material; S5. Preparation of coating material: Add the curing and crosslinking component to the composite coating base, stir evenly, and obtain the anti-calcium sulfate scale coating material as described in the first aspect.
[0019] The advantages and technical effects of the preparation method of the anti-calcium sulfate scale coating material in this embodiment of the invention are as follows: 1. Simple process and convenient operation: The embodiments of the present invention do not require complex equipment. They can be completed through conventional processes such as calcination pretreatment, liquid phase impregnation loading, mechanical mixing and dispersion, viscosity adjustment and filtration. The operating conditions of each step are mild (room temperature or medium and low temperature), and do not involve high temperature and high pressure or special atmosphere protection. The threshold for industrial implementation is low and it is easy to promote and apply.
[0020] 2. Pre-loading technology eliminates initial burst release: In this embodiment of the invention, the zinc ion active component is pre-loaded into the micropores and surface of the controlled-release regulating component to form a zinc ion controlled-release composite powder, which is then mixed with the film-forming matrix material. This effectively avoids the zinc ion active component being distributed in a free state in the coating, fundamentally eliminating the initial burst release phenomenon of zinc ions in traditional zinc-based coatings and ensuring water safety.
[0021] 3. Customizable Controlled-Release Regulating Component Structure: By controlling the calcination temperature (300–450℃), the pore structure parameters of the controlled-release regulating component can be precisely adjusted. Low-temperature calcination (300–350℃) preserves the complete microporous channels of the controlled-release regulating component, adapting to medium-to-high-speed zinc release conditions; high-temperature calcination (400–450℃) refines the pores of the controlled-release regulating component and enhances confinement resistance, adapting to low-speed, steady-state, long-term zinc release conditions, achieving controllable switching between different release rate requirements under the same preparation system.
[0022] 4. Good dispersion effect and uniform and dense coating: The process of step-by-step stirring and sand milling dispersion, combined with batch feeding, ensures that the zinc ion controlled release composite powder is uniformly dispersed in the film-forming matrix without agglomeration. The final coating structure is dense and has strong adhesion, ensuring the stable performance of long-term zinc release.
[0023] 5. Strong adaptability to construction: The viscosity of the coating material can be adjusted by an inert thinner, making it suitable for various coating methods such as spraying, brushing, and rolling, meeting the coating needs of the inner walls of industrial equipment of different shapes and sizes; it cures at room temperature, eliminating the need for heating equipment and reducing on-site construction energy consumption and costs.
[0024] Thirdly, embodiments of the present invention provide the application of the anti-calcium sulfate scale coating material described in the first aspect in preventing or inhibiting calcium sulfate scale formation in industrial equipment, wherein the industrial equipment is the inner wall of a power plant desulfurization wastewater treatment system, a circulating cooling water system, a heat exchange device, or a pipeline; the application includes coating the anti-calcium sulfate scale coating material onto the inner wall of the industrial equipment and curing it at room temperature to form an anti-calcium sulfate scale coating.
[0025] The advantages and technical effects brought about by the application of the embodiments of the present invention are as follows: 1. Simple construction and strong applicability: The anti-calcium sulfate scale coating material of the present invention can be applied to the inner metal wall of equipment by spraying, brushing or rolling, etc. It can be cured at room temperature and formed without heating equipment or special construction conditions. It is suitable for large-area anti-scaling coating of industrial equipment and pipelines of various shapes and sizes, and is especially suitable for scenarios where the on-site construction environment is limited.
[0026] 2. Long-lasting protection and low maintenance cost: Relying on the microporous confined slow-release mechanism of controlled-release regulating components, the anti-calcium sulfate scale coating can achieve uniform and long-lasting release of zinc ions, effectively overcoming the short-term failure defect of traditional zinc-based coatings, significantly extending the equipment anti-scaling maintenance cycle, reducing the frequency of downtime maintenance, and lowering system operating costs.
[0027] 3. Precisely adaptable to complex operating conditions: The dynamic release model can accurately predict the cumulative release of zinc ions under different times and operating conditions. Based on the scaling trends and operating parameters of different water qualities such as power plant desulfurization wastewater and circulating cooling water, the coating formula and thickness can be precisely matched to achieve quantitative control of anti-scaling performance and life prediction.
[0028] 4. Environmentally friendly and avoids the risk of exceeding standards: This application can predict the amount of zinc ions released into the water through dynamic models, effectively avoiding the risk of excessive zinc ion emissions, meeting environmental regulatory requirements, ensuring water safety, and demonstrating the application value of green scale prevention.
[0029] 5. Ensure safe operation and heat transfer efficiency of equipment: By effectively inhibiting the deposition of calcium sulfate scale on the inner wall of the equipment, the scale layer can prevent problems such as decreased heat transfer efficiency, increased energy consumption and pipeline blockage, thus ensuring the long-term safe, efficient and stable operation of industrial equipment.
[0030] Optionally, the single-coating dry film thickness is controlled within 80–200 μm, and cured at room temperature for 12–24 hours. Meeting the aforementioned conditions achieves a good balance between the long-term slow-release zinc ion reserve requirement and the coating's mechanical properties and ease of application. If the single-coating dry film thickness is too low, the total zinc ion loading is insufficient, resulting in a low maximum saturated release amount M0, which is detrimental to improving the scale inhibition life. If the single-coating dry film thickness is too high, the internal stress increases, making it prone to cracking and peeling during curing shrinkage or thermal expansion and contraction. Furthermore, an excessively long ion diffusion path may lead to a low release rate, affecting the scale inhibition effect. The aforementioned single-coating dry film thickness range ensures that the coating has sufficient zinc source reserves and uniform release channels, while also participating in release rate regulation through the thickness itself as the "ion diffusion path length"—the greater the thickness, the longer the path for zinc ions to migrate from the interior of the coating to the surface, resulting in a smoother release. This, in conjunction with the "matrix density regulation" in the four-dimensional regulation, achieves fine-tuning of the rate. Curing at room temperature for 12–24 hours does not rely on heating equipment, significantly reducing on-site construction energy consumption and costs. At the same time, this curing time ensures that the epoxy resin and amine or acid anhydride curing agents are fully cross-linked to form a dense, high-adhesion coating, ensuring the structural stability and continuous reliability of the coating under long-term high-salt, high-hardness wastewater scouring. Detailed Implementation
[0031] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0032] To address the technical problems of uncontrollable zinc ion release, short anti-scaling life, high cost, lack of quantitative control models, and poor targeted inhibition of calcium sulfate scale in existing zinc-based anti-scaling materials, this invention provides an anti-calcium sulfate scale coating material, its preparation method, and its application, which can achieve long-lasting, controllable, and predictable anti-calcium sulfate scale effect in industrial equipment.
[0033] 1. Anti-calcium sulfate scale coating material (1) Film-forming matrix material: selected from at least one of bisphenol A type E44 epoxy resin and bisphenol A type E51 epoxy resin, as the main film-forming skeleton of the coating, to ensure the adhesion, water resistance and structural stability of the coating; wherein the viscosity of bisphenol A type E44 epoxy resin and bisphenol A type E51 epoxy resin are 20000~25000mPa·s and 10000~15000mPa·s respectively, and can be flexibly selected according to the viscosity requirements of the process.
[0034] (2) Zinc ion active component: selected from at least one of zinc powder, zinc oxide, zinc sulfate, and zinc nitrate, with a particle size of 300-800 mesh, uniformly dispersed in the film-forming matrix material as a long-lasting zinc ion slow-release source; the amount of zinc ion active component added is 5wt%-30wt% of the mass of the film-forming matrix material, for example, 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 22wt%, 25wt%, 28wt%, 30wt%, etc., based on the mass of zinc element. The mass of zinc element is used as the measurement standard, that is, the mass of zinc element in the actual weighed zinc ion active component (at least one of zinc powder, zinc oxide, zinc sulfate, and zinc nitrate) accounts for 5wt%-30wt% of the mass of the film-forming matrix material. In other words, the zinc ion active component cannot be directly weighed according to the mass of "film-forming matrix material mass × 5%", but should be weighed according to the molecular formula of the selected zinc ion active component and its zinc element mass fraction. For example, if zinc oxide (ZnO, with a zinc element mass fraction of approximately 80.2%) is used, when the film-forming substrate material is 100 parts by mass, approximately 6.23 parts by mass of zinc oxide (approximately 5 / 0.802 ≈ 6.23 parts by mass) need to be weighed to achieve a zinc element mass of 5 wt% of the film-forming substrate material. If zinc sulfate heptahydrate (ZnSO4·7H2O, with a zinc element mass fraction of approximately 22.7%) is used, approximately 22.03 parts by mass (approximately 5 / 0.227 ≈ 22.03 parts by mass) need to be weighed to achieve a zinc element mass of 5 wt% of the film-forming substrate material. This measurement method ensures the comparability of different zinc sources under the same "zinc element mass" benchmark, allowing the total zinc ion release and coating scale prevention life to be uniformly predicted and controlled based on the total zinc element loading.
[0035] (3) Controlled-release regulating component: selected from at least one of porous inorganic carriers NaY molecular sieve and 13X molecular sieve; NaY and 13X molecular sieves have regular pores and a specific surface area ≥600m². 2 / g, possessing excellent zinc ion adsorption and loading capacity and micropore confinement regulation effect; the amount of controlled release regulating component added is 2wt% to 15wt% of the mass of the film-forming matrix material, such as 2wt%, 3wt%, 5wt%, 7wt%, 9wt%, 11wt%, 13wt%, 15wt%, etc.; the zinc ion slow release rate is precisely regulated through the micropore confinement effect.
[0036] (4) Curing and crosslinking components: Compatible with bisphenol A type E44 epoxy resin and bisphenol A type E51 epoxy resin, using at least one of amine curing agents and acid anhydride curing agents as curing and crosslinking components to achieve room temperature curing of the resin into a film. The total addition amount of the curing and crosslinking components is 15wt% to 25wt% of the mass of the film-forming matrix material, for example, 15wt%, 17wt%, 19wt%, 21wt%, 23wt%, 25wt%, etc. Among them, the amine curing agent is at least one of 650# polyamide curing agent and 651# polyamide curing agent. The amine value of 650# polyamide curing agent is 200 to 240 mg KOH / g and the viscosity is 3000 to 5000 mPa·s; the amine value of 651# polyamide curing agent is 380 to 420 mg KOH / g and the viscosity is 500 to 1000 mPa·s. The anhydride curing agent is selected from at least one of methyltetrahydrophthalic anhydride and hexahydrophthalic anhydride. The methyltetrahydrophthalic anhydride has a purity ≥98% and a viscosity of 50-80 mPa·s; the hexahydrophthalic anhydride has a purity ≥99.0% and a viscosity of 110-130 mPa·s.
[0037] (5) Inert diluent: Xylene and n-butanol are compounded to form an inert diluent with a mass ratio of (5-9):(1-5), such as 9:1, 8:2, 7:3, 6:4, 1:1, etc. The amount added is 5wt% to 20wt% of the mass of the film-forming matrix material, such as 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, etc. It is used to adjust the viscosity of the coating, has no reactive activity, and does not affect the coating structure and zinc release performance.
[0038] Furthermore, the anti-calcium sulfate scale coating material of this invention can precisely control Zn content. 2+ The sustained-release rate is 0.5~5.0 μg / (cm³). 2 •h) is suitable for long-term scale prevention in various high-salt and high-hardness wastewater conditions.
[0039] 2. Preparation method of anti-calcium sulfate scale coating material (1) Pretreatment of controlled-release conditioning components: The controlled-release conditioning components are calcined at 300-450℃ (e.g., 300℃, 320℃, 350℃, 370℃, 400℃, 420℃, 450℃, etc.) for 2-4 hours (e.g., 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, etc.) to remove adsorbed water and impurities from the pores, open up the microporous channels, and cool naturally to room temperature for later use, thereby improving the zinc ion adsorption loading capacity of the carrier; calcination at low temperature of 300-350℃ (e.g., 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, etc.) preserves the complete microporous channels. BET test shows that the specific surface area of the controlled-release conditioning components after calcination is 580-620 m². 2 / g (e.g., 580m) 2 / g、590m 2 / g、600m 2 / g、610m 2 / g、620m 2 / g, etc.), pore volume 0.38~0.42cm 3 / g (e.g., 0.38cm) 3 / g, 0.39cm 3 / g, 0.40cm 3 / g, 0.41cm 3 / g, 0.42cm 3 The average pore size is 2.8–3.2 nm (e.g., 2.8 nm, 2.9 nm, 3.0 nm, 3.1 nm, 3.2 nm, etc.), corresponding to a steady-state zinc ion release rate of 2.5–5.0 μg / (cm³). 2 ·h), for example 2.5μg / (cm 2 ·h), 3.0μg / (cm) 2 ·h), 3.5μg / (cm) 2 ·h), 4.0μg / (cm) 2 ·h), 4.5μg / (cm) 2 ·h), 5.0μg / (cm) 2 •h) and other suitable for medium- and high-speed zinc release conditions; high-temperature calcination at 400–450℃ (e.g., 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, etc.) refines the channels and increases the confinement resistance. BET test shows that the specific surface area of the controlled-release regulating component after calcination is 450–500 m². 2 / g (e.g., 450m) 2 / g、460m 2 / g、470m 2 / g、480m 2 / g、490m 2 / g、500m 2 / g, etc.), pore volume 0.25~0.30cm 3 / g (e.g., 0.25cm) 3 / g, 0.26cm 3 / g, 0.27cm 3 / g, 0.28cm 3 / g, 0.29cm 3 / g, 3.0cm 3The average pore size is 1.8–2.2 nm (e.g., 1.8 nm, 1.9 nm, 2.0 nm, 2.1 nm, 2.2 nm, etc.), corresponding to a steady-state zinc ion release rate of 0.5–2.0 μg / (cm²·h), such as 0.5 μg / (cm²·h), 1.0 μg / (cm²·h), 1.5 μg / (cm²·h), 2.0 μg / (cm²·h), etc., which is suitable for low-speed steady-state long-term zinc release conditions.
[0040] (2) Preloading of zinc ion active components: Disperse zinc ion active component powder in anhydrous ethanol solution to prepare a zinc-based dispersion with a mass fraction of 10% to 25% (e.g., 10%, 12%, 15%, 18%, 20%, 22%, 25%, etc.). Add the controlled-release adjustment component after calcination, and ultrasonically impregnate at a frequency of 30 to 50 kHz (30 kHz, 35 kHz, 40 kHz, 45 kHz, 50 kHz, etc.) at room temperature for 30 to 60 min (e.g., 30 min, 35 min, 40 min, 45 min, 50 min). After impregnation for 55 min, 60 min, etc., the mixture is stirred at room temperature (25-30℃) at 300-400 r / min (e.g., 300 r / min, 350 r / min, 400 r / min, etc.) for 2-4 h (e.g., 2 h, 3 h, 4 h, etc.) to uniformly load the zinc ion active component into the micropores and surface of the controlled-release regulating component. After impregnation, the mixture is dried at 80-100℃ (e.g., 80℃, 85℃, 90℃, 95℃, 100℃, etc.) for 5-8 h (e.g., 5 h, 6 h, 7 h, 8 h, etc.) to obtain zinc ion controlled-release composite powder. (3) Mixing and dispersing the film-forming matrix material: Place the film-forming matrix material in a stirred tank and stir at a low speed of 200-300 r / min (e.g., 200 r / min, 250 r / min, 300 r / min, etc.) for 3-8 min (e.g., 3 min, 4 min, 6 min, 8 min, etc.) at room temperature. Add zinc ion controlled-release composite powder in batches. Then increase the speed to 500-600 r / min (e.g., 500 r / min, 550 r / min, 600 r / min, etc.) and stir at a high speed for 30 minutes. After grinding for 15-30 minutes (e.g., 30 min, 35 min, 40 min, 45 min, 50 min, etc.) with zirconia grinding media at 1200-1400 r / min (e.g., 1200 r / min, 1300 r / min, 1400 r / min, etc.), ensure that the powder is uniformly dispersed in the film-forming matrix material without agglomeration. The particle size of the zirconia grinding media is 2-3 mm.
[0041] (4) Viscosity adjustment and modification: According to the process requirements, add inert diluent at a ratio of 5wt% to 20wt% (e.g., 5wt%, 10wt%, 15wt%, 20wt%, etc.) of the film-forming matrix material to adjust the viscosity of the coating. After stirring evenly, filter with a 200-mesh standard screen to remove trace impurities and large particle agglomerates to obtain a uniform composite coating base material. (5) Curing and film formation: Before preparing the coating, add the curing and crosslinking components according to the ratio, stir quickly and evenly, and apply evenly to the inner metal wall of the equipment by spraying, brushing or rolling. The thickness of the coating in a single dry film is controlled at 80-200μm (e.g. 80μm, 100μm, 120μm, 140μm, 160μm, 180μm, 200μm, etc.). Curing is carried out at room temperature for 12-24h (e.g. 12h, 15h, 18h, 20h, 22h, 24h, etc.) to form a dense, uniform, long-lasting slow-release anti-calcium sulfate scale coating.
[0042] 3. Dynamic model of zinc ion release Based on Fick's diffusion law and the confined slow-release mechanism of porous carriers, and combined with experimental fitting, a dynamic prediction model for zinc ion release of the anti-calcium sulfate scale coating of this invention is established. This model can accurately predict the cumulative release of zinc ions under different times and operating conditions, enabling quantitative control of anti-scaling performance and lifespan prediction. Cumulative release model: M t =M0×(1-e -kt ); Instantaneous release rate model: Vt=M0×k×(1-e -kt ); Where: M t This represents the cumulative release of zinc ions per unit area of the coating at time t, expressed in μg / cm³. 2 M0 represents the maximum saturated release of zinc ions from the coating, measured in μg / cm³. 2 The loading of zinc ion active components and the coating thickness determine the rate; k is the slow-release rate constant, with units of h. -1 t is the coating running time, in hours (h).
[0043] In this embodiment of the invention, the instantaneous release rate is stably controlled within 0.5–5.0 μg / (cm³) by regulating the k-value through micropore confinement of the controlled-release component. 2 ·h).
[0044] Based on this dynamic model, the coating formula can be accurately matched according to the actual water quality conditions, the effective life of the coating against scale can be predicted, and precise industrial application can be achieved. It can also predict the amount of zinc ions released into the water, effectively avoiding the risk of exceeding the standard.
[0045] 4. Precise control method for zinc ion release rate This invention achieves precise, continuous, and quantifiable control of the zinc ion release rate through a four-dimensional coupling approach involving structural regulation of the controlled-release component, control of the zinc source type and loading, control of the preparation process, and control of the matrix density. The rate can be precisely controlled from 0.5 to 5.0 μg / (cm³) according to different industrial scaling conditions. 2 •h) Targeted slow-release rate: This addresses the shortcomings of traditional zinc-based materials, such as uncontrollable release and inability to adapt to specific operating conditions. The specific control methods are as follows: (1) Structural regulation of controlled-release regulating components: Porous molecular sieves are used as controlled-release regulating components. By utilizing their regular micropore confinement effect, the diffusion resistance of the pores is changed by adjusting the amount of controlled-release regulating components added (2wt%~15wt%). The higher the amount of controlled-release regulating components, the greater the diffusion resistance of the pores, the smaller the rate constant k, and the smoother the release rate.
[0046] (2) Zinc source type and loading control: Differentiated matching of different zinc sources to suit different release ranges; insoluble zinc oxide is suitable for low-rate long-term sustained release (0.5~2.0μg / (cm)). 2 ·h), soluble zinc sulfate and zinc nitrate are suitable for medium-to-high-speed sustained release (2.0~5.0μg / (cm)). 2 By adjusting the zinc element loading (5wt%~30wt%), the maximum saturated release amount M0 can be changed, thereby achieving bidirectional control of the total release amount and release rate.
[0047] (3) Preparation process control: The slow-release performance is optimized by adjusting the calcination temperature, impregnation time and coating thickness of the components; low-temperature calcination at 300-350℃ preserves the complete microporous channels and is suitable for medium- and high-speed zinc release; high-temperature calcination at 400-450℃ refines the pore structure and enhances the confinement ability to achieve low-speed steady-state zinc release; extending the ultrasonic impregnation time can make the zinc components deeply embedded in the pores, eliminate free zinc on the surface and prevent the initial burst release phenomenon; the coating thickness is controlled at 80-200μm. The greater the thickness, the longer the ion diffusion path and the more gradual the release rate.
[0048] (4) Matrix density control: By adjusting the curing crosslinking component ratio and curing temperature, the crosslinking density of the film-forming matrix material can be controlled; a highly crosslinked and dense matrix can block the rapid penetration of water and reduce the zinc ion dissolution rate; moderately reducing the degree of crosslinking can improve the water molecule penetration efficiency, slightly increase the release rate, and achieve fine-tuning.
[0049] Based on the above four-dimensional control system, combined with the dynamic release model, the zinc ion release rate can be precisely customized under different operating conditions, ensuring stable scale inhibition effect, no zinc ion exceeding the standard, and predictable service life, making it suitable for complex high-hardness water quality systems such as desulfurization wastewater and circulating cooling water.
[0050] 5. Anti-scaling mechanism The anti-calcium sulfate scale coating formed after application of the anti-calcium sulfate scale coating material in this embodiment of the invention can achieve Zn by relying on the confined and slow-release mechanism of the porous controlled-release regulating component. 2+ Uniform and long-lasting release, inhibiting calcium sulfate scale formation through a dual synergistic mechanism of crystal nucleation inhibition and crystal distortion: (1) Crystal nucleation inhibition mechanism: slow release of Zn 2+ Precisely adsorbed onto the active sites on the surface of primary calcium sulfate crystal nuclei, interfering with Ca 2+ With SO4 2- Lattice matching significantly reduces the homogeneous nucleation rate of calcium sulfate, thus reducing scale formation at the source; (2) Crystal distortion mechanism: Zn 2+ By altering the surface charge distribution of calcium sulfate crystals and inducing crystal morphology distortion, a regular, dense, and strongly adhering hard scale layer cannot be formed. The loose and distorted micro crystals can be washed away by water flow, achieving long-lasting scale prevention.
[0051] 6. Application Method The anti-calcium sulfate scale coating of the present invention is uniformly applied to the inner wall of equipment and pipelines. After curing at room temperature, it can be used for a long time in industrial wastewater systems with high calcium and high sulfate content, so as to achieve long-term anti-calcium sulfate scale protection for equipment.
[0052] 7. Beneficial effects of the embodiments of the present invention: (1) Controllable and quantifiable zinc ion release: Using four-dimensional coupled controlled release technology, the zinc ion release rate can be precisely controlled and stabilized at 0.5–5.0 μg / (cm³). 2 •h), paired with a dedicated dynamic release model, can predict the release amount and material lifespan, completely solving the problems of explosive release pollution and excessively rapid decay of traditional zinc materials, and adapting to various differentiated scaling conditions.
[0053] (2) Long service life and good stability: Relying on the micropore confinement effect of porous controlled-release regulating components, zinc ions are released at a uniform rate for a long time, overcoming the short-term failure of traditional zinc-based materials and significantly extending the equipment anti-scaling maintenance cycle.
[0054] The present invention will now be described in detail with reference to the embodiments.
[0055] Example The following three embodiments share the same operating parameters, testing instruments and sampling methods, methods for measuring kinetic parameters k and M0, methods for calculating model fit, and methods for calculating the scale inhibition rate. Specifically: Operating parameters: The test medium is simulated high-salt, high-hardness wastewater, Ca 2+ Concentration 8000 mg / L, SO4 2-The system operates at a concentration of 12000 mg / L, a system pH of 7.5 ± 0.2, a water temperature of 25 ± 1℃, and a water circulation velocity of 0.8 m / s, maintaining constant temperature and flow throughout the process to avoid interference from environmental conditions on zinc release kinetics.
[0056] Testing Instruments and Sampling Methods: Inductively Coupled Plasma Mass Spectrometry (ICP-MS) was used to detect the zinc ion concentration in the aqueous solution. The cured coating samples were fixed in a circulating water tank, and samples were taken at regular intervals of 1h, 3h, 6h, 12h, 24h, 48h, 72h, 120h, 240h, and 720h to determine the Zn concentration in the aqueous solution at each time point. 2+ Concentration, combined with the effective coating area, yields the measured cumulative zinc ion release per unit area, M (μg / cm²). 2 ).
[0057] Method for fitting and determining kinetic parameters k and M0: The nonlinear least squares method was used to fit the measured time-cumulative release data, and the maximum saturated release M0 and the sustained release rate constant k were obtained by iterative solution.
[0058] Model fit calculation method: using the statistical coefficient of determination R. 2 The formula for calculating the goodness of fit between the release curve and the dynamic model is as follows:
[0059] Where: M 实测i The measured cumulative release at time point i is expressed in μg / cm³. 2 M 预测i Calculate the release amount for the corresponding time point in the model, in μg / cm³. 2 ; 实测i This is the average of all measured data, in μg / cm³. 2 The closer R² is to 1, the higher the model's accuracy in fitting the zinc ion release mechanism. Where M... 预测i The cumulative release model M established through the embodiments of the present invention t =M0×(1-e -kt ) was calculated.
[0060] Calculation method for scale inhibition rate: The scale deposition amount is accurately calculated by weighing method to obtain the scale inhibition rate data of each embodiment. The calculation formula and test method are as follows:
[0061] In the formula: η is the calcium sulfate scaling inhibition rate, in %; m0 is the scale deposition mass of the blank carbon steel test piece after 30 days, in mg / cm³. 2m1 represents the scale deposition mass of the specimen coated with the anti-calcium sulfate scale coating material of this embodiment after 30 days, in mg / cm³. 2 .
[0062] Example 1: Low-speed sustained-release formulation A zinc ion-loaded anti-calcium sulfate scale coating material is composed of the following components: 100 parts by weight of bisphenol A type E44 epoxy resin, 5 parts by weight of 300-800 mesh zinc oxide (based on the elemental mass of zinc), 15 parts by weight of NaY molecular sieve, 20 parts by weight of 650# polyamide curing agent, and 12 parts by weight of inert diluent (xylene to n-butanol in a mass ratio of 7:3).
[0063] Coating preparation method: NaY molecular sieve was calcined at 400℃ for 3 hours and then naturally cooled to room temperature to obtain the controlled-release regulating component after calcination; Zinc oxide powder was dispersed in anhydrous ethanol to prepare a zinc-based dispersion with a mass fraction of 20%. A calcined controlled-release regulating component was added to the zinc-based dispersion, and the mixture was ultrasonically impregnated at 40 kHz and 25 °C for 40 min. Then, it was stirred at 350 r / min for 3 h at 25 °C and dried at 90 °C for 6 h to obtain zinc ion controlled-release composite powder. Bisphenol A type E44 epoxy resin was placed in a mixing tank, and zinc ion controlled-release powder was added to the bisphenol A type E44 epoxy resin in batches. The mixture was stirred at 250 r / min for 5 min, and then the speed was increased to 550 r / min for 40 min. The mixture was then dispersed by milling at 1300 r / min for 20 min using zirconia sand mill media to obtain a mixture. 12 parts of inert diluent were added to the mixture to adjust the viscosity of the coating material. After stirring evenly, the mixture was filtered through a 200-mesh standard screen. Finally, the curing agent was added and stirred evenly. The mixture was sprayed onto a carbon steel test plate, with the coating thickness controlled at 200 μm, and cured at room temperature for 24 h.
[0064] Test results: Steady-state zinc ion release rate of the coating is 0.5 μg / (cm³). 2 ·h), in the low-speed long-term slow-release range, the release curve fits the dynamic model by 98.5%; under high calcium and high sulfate conditions, after 30 days of continuous operation, the calcium sulfate scaling inhibition rate is 92.1%, and there is no obvious scale deposition.
[0065] Example 2: Medium-rate release formulation A zinc ion-loaded anti-calcium sulfate scale coating material is composed of the following components: 100 parts by weight of bisphenol A type E44 epoxy resin, 15 parts by weight of 300-800 mesh zinc sulfate (based on the mass of zinc element), 8 parts by weight of 13X molecular sieve, 20 parts by weight of methyltetrahydrophthalic anhydride curing agent, and 12 parts by weight of inert diluent (xylene to n-butanol in a mass ratio of 7:3).
[0066] Coating preparation method: NaY molecular sieve was calcined at 350℃ for 3h and naturally cooled to room temperature to obtain the controlled-release regulating component after calcination; the subsequent process was the same as in Example 1, controlling the coating thickness to 130μm and curing at room temperature for 24h.
[0067] Tested under the same conditions as in Example 1, the steady-state release rate of zinc ions was 2.8 μg / (cm³). 2 •h), adapted to conventional scaling conditions, the release curve fits the dynamic release model with a degree of 98.2%; the calcium sulfate scaling inhibition rate is 90.3% after 30 days, the coating does not peel off or powder, and the release stability is excellent.
[0068] Example 3: High-speed release formulation A zinc ion-loaded anti-calcium sulfate scale coating material is composed of the following components: 100 parts by weight of bisphenol A type E51 epoxy resin, 300-800 mesh zinc sulfate (30 parts by weight of zinc element), 2 parts by weight of 13X molecular sieve, 20 parts by weight of methyltetrahydrophthalic anhydride curing agent, and 12 parts by weight of inert diluent (xylene to n-butanol in a mass ratio of 7:3).
[0069] Coating preparation method: NaY molecular sieve was calcined at 300℃ for 3h and then naturally cooled to room temperature to obtain the controlled-release regulating component after calcination; the subsequent process was the same as in Example 1, controlling the coating thickness to 80μm and curing at room temperature for 24h.
[0070] Tested under the same conditions as in Example 1, the steady-state release rate of zinc ions was 4.8 μg / (cm³). 2 •h) It is suitable for heavy scaling conditions in desulfurization wastewater of power plants. The release curve fits the dynamic release model with a degree of 97.6%. It has a fast short-term scale inhibition rate, with a calcium sulfate scale inhibition rate of 89.6% in 30 days, and can quickly inhibit the formation of calcium sulfate crystal nuclei.
[0071] Comparative Example 1: Ordinary zinc coating material without controlled-release regulating components The coating material consists of the following components: 100 parts by weight of bisphenol A type E44 epoxy resin, 5 parts by weight of 300-800 mesh zinc oxide (based on elemental zinc content), 20 parts by weight of 650# polyamide curing agent, and 12 parts by weight of inert diluent (xylene to n-butanol in a mass ratio of 7:3). No NaY molecular sieve is added; the rest of the preparation process and testing conditions are completely consistent with Example 1.
[0072] Tested under the same conditions as in Example 1, the initial zinc ion release rate was as high as 11.8 μg / (cm³). 2 •h) There is a risk of water exceeding the standard; after 7 days of operation, the zinc ion release rate decreases significantly, and the calcium sulfate scaling inhibition rate is only 57.4% after 30 days. The long-term scale prevention performance is extremely poor, and the release is irregular and cannot be quantitatively predicted.
[0073] Comparative Example 2: Coating with parameters exceeding the range The coating material is the same as that in Example 1, except that it contains 15 parts by weight of NaY molecular sieve and 35 parts by weight of 300-800 mesh zinc oxide. The coating preparation method is the same as in Example 1.
[0074] Tested under the same conditions as in Example 1, the results showed that the powder agglomerated severely, resulting in poor coating density; the release of zinc ions was disordered, with the release rate fluctuating; the model fit was less than 80%, and the anti-scaling stability was significantly reduced.
[0075] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0076] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.
Claims
1. A coating material resistant to calcium sulfate scale, characterized in that, The anti-calcium sulfate scale coating material comprises the following components: (1) Film-forming matrix material: The film-forming matrix material is bisphenol A type epoxy resin; (2) Zinc ion active component: The zinc ion active component is selected from at least one of zinc powder, zinc oxide, zinc sulfate and zinc nitrate; the amount of zinc ion active component added is 5wt% to 30wt% of the mass of the film-forming matrix material, based on the mass of zinc element. (3) Controlled-release regulating component: The controlled-release regulating component is a molecular sieve; the amount of the controlled-release regulating component added is 2wt% to 15wt% of the mass of the film-forming matrix material; (4) Curing and crosslinking components: The curing and crosslinking components are selected from amine curing agents and / or acid anhydride curing agents; the amount of the curing and crosslinking components added is 15wt% to 25wt% of the mass of the film-forming matrix material; (5) Inert diluent: The inert diluent is a mixture of xylene and n-butanol; The amount of the inert diluent added is 5 wt% to 20 wt% of the mass of the film-forming matrix material.
2. The anti-calcium sulfate scale coating material according to claim 1, characterized in that, The film-forming matrix material is selected from bisphenol A type E44 epoxy resin and / or bisphenol A type E51 epoxy resin.
3. The anti-calcium sulfate scale coating material according to claim 1, characterized in that, The particle size of the zinc ion active component is 300-800 mesh.
4. The anti-calcium sulfate scale coating material according to claim 1, characterized in that, The controlled-release regulating component is selected from NaY molecular sieve and / or 13X molecular sieve.
5. The anti-calcium sulfate scale coating material according to claim 1, characterized in that, The amine curing agent is selected from 650# polyamide curing agent and / or 651# polyamide curing agent; the acid anhydride curing agent is selected from methyltetrahydrophthalic anhydride and / or hexahydrophthalic anhydride.
6. The anti-calcium sulfate scale coating material according to claim 1, characterized in that, In the inert diluent, the mass ratio of xylene to n-butanol is (5-9):(1-5).
7. The anti-calcium sulfate scale coating material according to claim 1, characterized in that, The steady-state release rate of zinc ions from the anti-calcium sulfate scale coating material is 0.5–5.0 μg / (cm²·h).
8. The method for preparing the anti-calcium sulfate scale coating material according to any one of claims 1 to 7, characterized in that, The preparation method of the anti-calcium sulfate scale coating material includes the following steps: S1. Pretreatment of controlled-release regulating component: The controlled-release regulating component is calcined at 300-450℃ for 2-4 hours and then naturally cooled to room temperature to obtain the calcined controlled-release regulating component; S2. Preloading of zinc ion active components: The zinc ion active components are dispersed in anhydrous ethanol to prepare a zinc-based dispersion with a mass fraction of 10% to 25%. The calcined controlled-release regulating components are added to the zinc-based dispersion, and the mixture is ultrasonically impregnated at room temperature for 30 to 60 minutes. Then, the mixture is stirred at room temperature at a speed of 300 to 400 r / min for 2 to 4 hours. After impregnation, the mixture is dried to obtain zinc ion controlled-release composite powder. S3. Mixing and dispersing the film-forming matrix material: Place the film-forming matrix material in a stirring vessel and stir at 200-300 r / min for 3-8 min at room temperature. Add the zinc ion controlled-release composite powder in batches, then stir at 500-600 r / min for 30-50 min, and then disperse by sand milling for 15-30 min to obtain the mixture. S4. Viscosity adjustment and modification: Add the inert diluent to the mixture to adjust the viscosity, stir evenly and then sieve to obtain the composite coating base material; S5. Preparation of coating material: Add the curing and crosslinking component to the composite coating base, stir evenly, and obtain an anti-calcium sulfate scale coating material.
9. The application of the anti-calcium sulfate scale coating material according to any one of claims 1 to 7 in preventing or inhibiting calcium sulfate scale formation in industrial equipment, characterized in that, The industrial equipment is the inner wall of a power plant desulfurization wastewater treatment system, a circulating cooling water system, a heat exchange equipment, or a pipeline; the application includes coating the anti-calcium sulfate scale coating material onto the inner wall of the industrial equipment, curing it at room temperature to form an anti-calcium sulfate scale coating.
10. The application according to claim 9, characterized in that, The thickness of the coating in a single dry film is controlled at 80–200 μm, and it is cured at room temperature for 12–24 hours.
